ESTIMASI EMISI KARBON DARI KONSUMSI LISTRIK DAN SAMPAH: STUDI KASUS PASAR BULU - Yeremia Petra Sigalingging; Tegar Hermawan; Talenta Vena Insani; Penesta Tia Tira Sinulingga; Melinda Fitria; Clara Febina Tarigan; Yasmien Mumtaz Azzahra; Indah Susilowati (Universitas Nias Raya, 2026)
Traditional markets play an important role in urban economic systems while simultaneously contributing to greenhouse gas emissions through electricity consumption and solid waste generation. Pasar Bulu, a major traditional market in Semarang City with high trading intensity and near-continuous daily operations, represents a significant source of urban carbon emissions. This study aims to quantify carbon emissions originating from electricity consumption and solid waste generation at Pasar Bulu and to analyze the dominant sources contributing to the market’s overall carbon footprint. A mixed-methods approach was employed by integrating quantitative measurements and qualitative analysis. Quantitative data were obtained from electricity consumption records of market facilities and traders’ stalls, as well as annual waste volume and composition data. Qualitative data were collected through field observations and in-depth interviews with 36 respondents representing academics, business actors, government officials, and community groups (ABGC). Carbon emission estimates were calculated using the IPCC Guidelines for National Greenhouse Gas Inventories (2006), applying the energy sector method for indirect emissions from electricity consumption and the First Order Decay (FOD) method for solid waste emissions. The results show that electricity consumption generated 15,522.83 kg CO₂, primarily originating from centralized market installations and stalls using intensive lighting and cooling equipment. Meanwhile, solid waste management produced 1,089.66 tons CO₂ per year, dominated by food waste emissions amounting to 958.83 kg CO₂, driven by methane formation during organic waste decomposition. These findings indicate that although electricity consumption constitutes the largest source of carbon emissions in absolute terms, food waste remains a critical emission component within the waste sector. Therefore, carbon mitigation strategies in Pasar Bulu should prioritize electricity efficiency improvements alongside source-based organic waste management to support sustainable and low-carbon traditional market operations